2018
DOI: 10.1016/j.jinteco.2018.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Tariffs and markups in retailing

Abstract: Conventional wisdom suggests that domestic manufacturers benefit from cost advantages vis-á-vis their foreign rivals. Tariffs on imported products or exchange rate depreciations are typically expected to raise relative prices of foreign goods and shift residual demands of domestic substitutes outwards. Here we show that these changes in wholesale/manufacturing prices can be offset and even dominated by adjustments in retail markups. Retailers have an incentive to charge the highest markups for low-cost product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Our results suggest that retailers are absorbing a significant share of the increase in the cost of affected imports by accepting lower profit margins on those goods. 4 This empirical evidence supports the idea that a more complete understanding of the full supply chain, from "at-the-dock" importers through to final retailers, is important to capture the full implications of any trade policy, a point made theoretically in Cole and Eckel (2018).…”
mentioning
confidence: 59%
“…Our results suggest that retailers are absorbing a significant share of the increase in the cost of affected imports by accepting lower profit margins on those goods. 4 This empirical evidence supports the idea that a more complete understanding of the full supply chain, from "at-the-dock" importers through to final retailers, is important to capture the full implications of any trade policy, a point made theoretically in Cole and Eckel (2018).…”
mentioning
confidence: 59%
“…Our results suggest that retailers are absorbing a significant share of the increase in the cost of affected imports by earning lower profit margins on those goods. 4 This empirical evidence supports the idea that a more complete understanding of the full supply chain, from "at-the-dock" importers through to final retailers, is important to capture the full implications of any trade policy, a point made theoretically in Cole and Eckel (2018).…”
Section: Introductionmentioning
confidence: 59%
“…Rong and Xu [6] assessed the impact of manufacturer altruistic preferences and government subsidies on the multinational green supply chain under dynamic tariffs. Cole et al [7] showed that the price rise effect of retailers would affect the price transmission of tariffs to other goods along the supply chain. Cipollina et al [8] studied the impact of EU agricultural tariff policy on agricultural product imports and found that the tariff reduction directly increased the import volume of products.…”
Section: Literature Reviewmentioning
confidence: 99%